A PNF Intervention Strategy with ICF Tool Applied for Improvement of Dressing in a Patient with Rotator Cuff Syndrome : A Case Report (Global Journal of Science Frontier Research, 2020)
Purpose: This study was conducted to investigate the intervention effect obtained by applying an ICF tool to improve the dressing in a patient with rotator cuff syndrome to schematize the problems and approaching with PNF to solve the problems. Methods: The subject of this study was a 44-year-old patient who underwent surgery after complete right rotator cuff tear. To treat his symptoms, the processes of clinical practice were implemented in the order of examination, assessment, diagnosis, prognosis, intervention, and outcome. During examination, patient information was collected using the ICF core set. In the assessment, the problems were schematized, and an ICF assessment sheet was used to identify the interaction of the problems. The diagnosis was made by clearly describing the causal relationship derived from the assessment in ICF terms. To solve the problems, the intervention was given in the order of indirect, direct, and task based on the philosophy of PNF. To evaluate the outcome, the differences before and after the intervention were compared. Additionally, the comparison for the ICF qualifier is presented with the ICF evaluation display. Results: The results of the study showed clinical advantages in shoulder strength, eccentric control, range of motion, scapular stability, and shoulder pain. Overall, our patient with rotator cuff syndrome showed improvement in dressing and undressing activity in response to the PNF strategy. Conclusion: Application of the PNF intervention strategy after complete rotator cuff tear would have a positive effect on patient upper extremity function.
Keywords: dressing; intenational classification of functioning disability and health; prioproceptive neuromuscular facilitation